KINETIC MODELING OF AMMONIA SELECTIVE CATALYTIC REDUCTION FOR CLEANING EMISSIONS FROM VEHICLES: CATALYST AGING - , SUPRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ammonia Selective Catalytic Reduction (NH3-SCR) is an established technology to reduce NOx for heavy-duty vehicles. Metal exchanged zeolites, such as copper zeolites, are used for NH3-SCR. The effects of hydrothermal aging over zeolite based catalyst are recently studied. However, there are no kinetic models present that can describe aging over copper zeolites. This project aims to develop kinetic modeling of NH3-SCR over Cu-Beta. In a previous master thesis work experiments for studying aging of NH3-SCR over Cu- Beta was conducted. The main reactions that were previously examined experimentally were ammonia storage, ammonia oxidation, NO oxidation, standard SCR, rapid SCR, NO2 SCR and N2O formation. The results of the experiments were then used to construct the kinetic model. We suggest that some of the different reactions that occur in the SCR mechanism take place on different sites. We have therefore introduced aging factors that we multiply the pre-exponential factors with. We suggest that different sites have different aging factors. In this way we can group the reactions after on which sites the reactions occur. This will also result in a fast way of tuning aging models since we only need to determine NH3 storage/desorption and the aging factors. The results showed that the simulation approach worked well for modeling the experimental results. For ammonia TPD the simulations are enough with only decreasing storage capacity of ammonia and using heat of adsorption measured by microcalorimeter. Our model can describe that the higher temperature of hydrothermal aging gives reducing of ammonia storage at higher temperature as well as decreased temperature for NH3 desorption. For NH3 oxidation, NO oxidation and NH3-SCR a Cu-beta catalyst which was aged between 500oC and 800oC was described with three aging factors. Meanwhile aged catalyst at 900oC has a particular behavior for tuning aging factors due to that the structure has collapsed at this high temperature. In addition N2O formation occurred both at low temperature and at high temperature and a model was developed for this.